Adaptation of Rating System for Sustainable Housing and Settlements in Indonesia - Hidayatullah Santius, Syarif (KnE Social Sciences, 2019)
This paper describes the process of identification, weighting, and validation of assessment criteria for the sustainable housing and settlements rating system. The assessment criteria in this rating system divided into two categories, i.e., the environmental quality and load. The rating system criteria were selected using the Delphi Method, and their weight coefficients were obtained using Analytical Hierarchy Process (AHP). There are 37 criteria resulted from Delphi Consensus and grouped into the environmental quality and load category. The weight coefficients for three main criteria in the environmental quality category consist of (1) microclimate control and ecosystem conservation (0.439), (2) improvement of service function (0.384) and (3) improvement of citizen’s welfare (0.177). The weight coefficients for three main criteria in the environmental load category consist of (1) reduction of the environmental load to other areas (0.432), (2) reduction of infrastructure load (0.381), and (3) environmental management (0.187). These criteria and their weight coefficients were then validated to obtain a correlation coefficient between rating values and citizen satisfaction. The validation result shows a positive and strong correlation. The rating system can be used by local governments to identify the sustainability level and to determine suitable development policies.